Identification of children at risk of influenza-related complications in primary and ambulatory care: a systematic review and meta-analysis. Issue 2 (February 2015) - Gill, Peter J; Ashdown, Helen F; Wang, Kay; Heneghan, Carl; Roberts, Nia W; Harnden, Anthony; Mallett, Susan
Summary: Background: Interventions to prevent influenza-related complications are recommended for individuals at the greatest risk of serious clinical deterioration. However, guidelines are based on consensus opinion rather than evidence, and do not specify risk factors in children. We aimed to provide an evidence-based definition of children who are most at risk of such complications. Methods: In this systematic review, we searched the Medline and Medline In Process, Embase, Science Citation Index, and CINAHL databases for studies published between inception and April 3, 2013. We included studies that reported data for underlying disorders and complications in children presenting in primary or ambulatory care with influenza or influenza-like illness. We requested unpublished data from investigators of studies that had obtained, but not published, relevant data. We analysed data with univariable meta-analysis and individual patient data multivariable meta-analysis methods. The primary outcome was admission to hospital as a proxy for complications of influenza or influenza-like illness. Findings: We included 28 articles that reported data from 27 studies (14 086 children). Strong risk factors for hospital admission were neurological disorders (univariable odds ratio [OR] 4· 62, 95% CI 2·82–7·55), prematurity (4·33, 2·47–7·58), sickle cell disease (3·46, 1·63–7·37), immunosuppression (2·39, 1·24–4·61), diabetes (2·34, 1·20–4·58), and age younger than 2 years (2·51, 1·71–3·69). However, reactive airways disease including asthma (1·36, 0·82–2·26) and obesity (0·99, 0·61–1·62) were not found to be risk factors. On the basis of individual patient data multivariable analysis (1612 children, four studies), the risk of hospital admission was higher in children with more than one risk factor than in children with just one risk factor, when age younger than 2 years was included as a risk factor (92 [74%] of 124 vs 428 [52%] of 817; difference 22%, 95% CI 13–30%, p<0·0001). Interpretation: We identified prematurity as a new strong risk factor for influenza-related complications in children. Our findings also support the inclusion of neurological disorders, sickle cell disease, immunosuppression, diabetes, and age younger than 2 years as risk factors in existing guidelines. Interventions to prevent influenza-related complications should be prioritised in these groups, but should also be considered for other children, especially those with more than one risk factor or severe underlying comorbidities. Funding: UK National Institute for Health Research.